2019
DOI: 10.3389/fonc.2019.01267
|View full text |Cite
|
Sign up to set email alerts
|

Omental Tissue-Mediated Tumorigenesis of Gastric Cancer Peritoneal Metastases

Abstract: The peritoneal cavity, especially the omentum, is a common site for gastric cancer metastasis, representing advanced disease stage and poor prognosis. Here, we studied the effects of omental tissue on gastric cancer tumor progression in vitro and in vivo. Utilizing in vitro models, we found that omental tissue secreted factors increased gastric cancer cellular growth (by 30–67%, P < 0.05), motility (>8-fold, P < 0.05), invasiveness (>7-fold, P < 0.05) and chemoresistance to platinum-based chemotherapeutic agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Although GC-derived exosomes have been largely studied since the first characterization decades ago [20], the publications on the regulation of GC angiogenesis are limited. So far, a few of cargoes including CD44, CCR6, HER-2/neu [21] and several cytokines [22] were identified in GC-derived exosomes, and miR-130a/C-MYB [23], miR-135b/FOXO1 [24], miR-155/FOXO3 [25] and HGF [26] were, respectively, uncovered to be potential signals for exosome-HUVEC interactions. Given that the complex compositions including receptors, transcription factors, enzymes, extracellular matrix proteins, lipids, nucleic acids (DNA, mRNA, and miRNA) constitute exosomes, far further declarations on the complex working mechanisms of exosomes in GC angiogenesis are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although GC-derived exosomes have been largely studied since the first characterization decades ago [20], the publications on the regulation of GC angiogenesis are limited. So far, a few of cargoes including CD44, CCR6, HER-2/neu [21] and several cytokines [22] were identified in GC-derived exosomes, and miR-130a/C-MYB [23], miR-135b/FOXO1 [24], miR-155/FOXO3 [25] and HGF [26] were, respectively, uncovered to be potential signals for exosome-HUVEC interactions. Given that the complex compositions including receptors, transcription factors, enzymes, extracellular matrix proteins, lipids, nucleic acids (DNA, mRNA, and miRNA) constitute exosomes, far further declarations on the complex working mechanisms of exosomes in GC angiogenesis are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs are dysregulated and play a role in the peritoneal metastasis of gastric cancer [188]. Mechanisms of interaction between peritoneally metastasizing cancer cells and the omentum seem to be common in ovarian and gastric cancers, as well as in PDA [127,189,190]. This convergence attests to a conserved symbiotic relation between cancer cells and mesothelium.…”
Section: Establishment Of Metastatic Depositsmentioning
confidence: 98%
“…In addition to exosomal information transfer from tumor cells, there is also crosstalk between healthy tissues and tumor cells. A proteomic study confirmed the role of omental exosomes in the growth of gastric cancer and the development of peritoneal metastases [ 69 ]. In the circulation, microRNAs can not only be found in exosomes or microvesicles, but also in a protein-bound state.…”
Section: The Role Of Liquid Biopsy In Gastric Cancer In the Early Detection Of Metastatic Diseasementioning
confidence: 99%